2013
DOI: 10.3141/2365-05
|View full text |Cite
|
Sign up to set email alerts
|

Naturalistic Driving Observations of Manual and Visual–Manual Interactions with Navigation Systems and Mobile Phones While Driving

Abstract: This paper discusses a naturalistic driving study on the use of mobile phones and navigation systems while driving. Manual interactions with these devices while driving can cause distraction from the driving task and reduce traffic safety. In this study 21 subjects were observed for 5 weeks. Their behavior was logged by four cameras, a Global Positioning System sensor, and a number of additional sensors. Results are presented on the durations and frequencies of manual interactions with the mobile phone and nav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 13 publications
1
6
1
Order By: Relevance
“…The values found in this study resemble those of other international NDS, highlighting the seriousness of MPU. International comparisons indicate the average time spent engaged in visual-manual MPU (I 1 ) of 28.46 s ( SD = 47.71 s) is similar to the average time of 31 s found in a Netherlands naturalistic study [ 16 ] and the average time of 30 s found in a North American naturalistic study carried out in Detroit, MI [ 13 ]. For the German study, the I 1 value was 46 s [ 18 ].…”
Section: Discussionsupporting
confidence: 65%
See 3 more Smart Citations
“…The values found in this study resemble those of other international NDS, highlighting the seriousness of MPU. International comparisons indicate the average time spent engaged in visual-manual MPU (I 1 ) of 28.46 s ( SD = 47.71 s) is similar to the average time of 31 s found in a Netherlands naturalistic study [ 16 ] and the average time of 30 s found in a North American naturalistic study carried out in Detroit, MI [ 13 ]. For the German study, the I 1 value was 46 s [ 18 ].…”
Section: Discussionsupporting
confidence: 65%
“…[ 46 ]. The average percentage of trips with MPU while driving (I 2 ) of 58.71% ( SD = 25.80%) was much higher than the value of 13% found in a Swedish NDS [ 20 ], higher than that found in two studies in the Netherlands, an older one with 40% [ 16 ] and a more recent one with 32% [ 17 ]. However, the present Brazilian result (I 2 ) is similar to the results of the German NDS that found MPU in 56% of the trips [ 18 ].…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…A recent naturalistic driving study showed that manual interaction with the navigation system accounts for approximately 1% of total driving time (Christoph, van Nes, & Knapper, 2013). According to Green (1999), it takes 1-2.5 min to enter a destination.…”
Section: Objectivesmentioning
confidence: 99%